New tine to save time - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
A new cultivating tine will enable farmers in Burkina Faso to cultivate their lands before the rains break, and therefore to plant their millet much earlier. This should lead to higher yields as the crops will get the benefit of a longer growing...